The Effect of Employment Protection on Firms' Worker Selection - Sebastian Butschek; Jan Sauermann (Institute of Labor Economics (IZA), 2019)
To estimate the causal effect of employment protection on firms' worker selection, we study a policy change that reduced dismissal costs for the employers of over a tenth of Sweden's workforce. Our difference-in-differences analysis of firms' hiring uses individual ability measures including estimated worker fixed effects and cognitive test scores. We find that the reform reduced minimum hire quality by 5% of a standard deviation, half of which we can attribute to firms' hiring becoming more selective. Our results help discriminate between existing theories, supporting the prediction that firms shift their hiring standards in response to changes in dismissal costs.
Keywords: M51; D22; J24; J38; 330; worker selection; screening; hiring standard; employment protection; dismissal costs